4-week eicosapentaenoic acid-rich fish oil supplementation partially protects muscular damage following eccentric contractions. Issue 1 (1st March 2021) - Tsuchiya, Yosuke; Ueda, Hisashi; Yanagimoto, Kenichi; Kato, Ayaka; Ochi, Eisuke
Abstract: Background: We previously showed 8-week of fish oil supplementation attenuated muscle damage. However, the effect of a shorter period of fish oil supplementation is unclear. The present study investigated the effect of fish oil, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), for 4 weeks on muscular damage caused by eccentric contractions (ECCs) of the elbow flexors. Methods: Twenty-two untrained men were recruited in this double-blind, placebo-controlled, parallel design study and the subjects were randomly assigned to the EPA and DHA group (EPA and DHA, n  = 11) and placebo group (PL, n  = 11). They consumed either EPA 600 mg and DHA 260 mg per day or placebo supplement for 4 weeks prior to exercise. Subjects performed 60 ECCs at 100 % maximal voluntary contraction (MVC) using a dumbbell. Changes in MVC torque, range of motion (ROM), upper arm circumference, muscle soreness, echo intensity, muscle thickness, serum creatine kinase (CK), and interleukin-6 (IL-6) were assessed before exercise; immediately after exercise; and 1, 2, 3, and 5 days after exercise. Results: ROM was significantly higher in the EPA and DHA group than in the PL group immediately after performing ECCs ( p  < 0.05). No differences between groups were observed in terms of MVC torque, upper arm circumference, muscle soreness, echo intensity, and thickness. A significant difference was observed in serum CK 3 days after ECCs ( p  < 0.05). Conclusions: We concluded that shorter period EPA and DHA supplementation benefits joint flexibility and protection of muscle fiber following ECCs.